Comparative evaluation of boron distribution from ulexite, colemanite and DOT rods in Scots pine wood - Kartal, Saip Nami; Terzi, Evren; Figen, Aysel Kanturk; Cordan, Melek; Aydin, Secil; Piskin, Sabriye (NORTHEAST FORESTRY UNIV, 2021)
This study evaluated boron diffusion from rods made of raw boron minerals, ulexite and colemanite with low water solubility, in comparison with di-sodium octaborate tetrahydrate (DOT). Scots pine (Pinus sylvestris L.) sapwood and heartwood blocks were conditioned to target moisture contents of 30%, 60%, and 90%. The rods were inserted into the blocks through treatment holes and boron diffusion was observed at three assay zones across the blocks after 7, 30, 60 and 90-day-incubation at room temperature. Ethylene glycol was also inserted into the holes to improve boron diffusion. Boron levels increased with increased wood moisture content. With some exceptions, boron in the assay zones did not tend to follow consistent amount gradients with distance from the treatment hole. Boron levels from ulexite rods were higher than those from colemanite rods, with DOT rods with the highest diffusion rates as a result of higher water solubility of DOT than ulexite and colemanite. The results suggest that ulexite-based rods may be useful in the presence of ethylene glycol in sapwood when wood is at high moisture content for extended periods.
Keywords: Boron rods; Remedial; Ulexite; Colemanite; Distribution; DOT; DOUGLAS-FIR; MOISTURE-CONTENT; DIFFUSION; BORATE; PERFORMANCE; MOVEMENT; FLUORIDE; Forestry